Impact of ghrelin on vitreous cytokine levels in an experimental uveitis model - Turgut B; Gul FC; Dagli F; Ilhan N; Ozgen M (Dove Medical Press, 2013)
Burak Turgut,1 Fatih Cem Gül,1 Ferda Dağli,2 Nevin Ilhan,3 Metin Özgen41Department of Ophthalmology, School of Medicine, Firat University, Elazig, 2Department of Pathology, School of Medicine, İnönü University, Malatya, 3Department of Biochemistry, School of Medicine, Firat University, Elazig, 4Department of Rheumatology, School of Medicine, İnönü University, Malatya, TurkeyBackground: The purpose of this study was to investigate the effect of intraperitoneal ghrelin on vitreous levels of interleukin (IL)-1, IL-6, and tumor necrosis factor-alpha (TNF-α) and to compare its effects with those of intraperitoneal infliximab in an experimental uveitis model.Methods: Twenty-four male rats were assigned to four groups of six rats in each. All the rats, except for those in group 1 (controls), were injected intravitreally with concanavalin A to induce experimental uveitis. Rats in group 2 (sham) were not given any treatment after uveitis was induced. Rats in group 3 were given intraperitoneal infliximab 0.5 mg/100 mL on days 0, 1, 3, 5, and 7 following induction of uveitis on day 14 of the study. Rats in group 4 were given intraperitoneal ghrelin 10 ng/kg/day for 7 days following induction of uveitis. On day 21 of the study, enucleated globes were subjected to histopathologic examination. Vitreous levels of IL-1, IL-6, and TNF-α were measured by enzyme-linked immunosorbent assay.Results: Vitreous levels of IL-1, IL-6, and TNF-α were significantly increased in the sham group relative to the control group (P < 0.05), but showed a significant decrease in the group treated with infliximab (P < 0.05). Cytokine levels also decreased in the ghrelin-treated group, but the decrease was not statistically significant (P > 0.05).Conclusion: Ghrelin failed to decrease the IL-1, IL-6, and TNF-α levels that play a critical role in the pathogenesis of uveitis.Keywords: uveitis, tumor necrosis factor-alpha, interleukin-1, interleukin-6, infliximab, ghrelin